2010
DOI: 10.1186/1423-0127-17-92
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous and exogenous stem cells: a role in lung repair and use in airway tissue engineering and transplantation

Abstract: Rapid repair of the denuded alveolar surface after injury is a key to survival. The respiratory tract contains several sources of endogenous adult stem cells residing within the basal layer of the upper airways, within or near pulmonary neuroendocrine cell rests, at the bronchoalveolar junction, and within the alveolar epithelial surface, which contribute to the repair of the airway wall. Bone marrow-derived adult mesenchymal stem cells circulating in blood are also involved in tracheal regeneration. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 85 publications
3
28
0
1
Order By: Relevance
“…In many studies, ASC engraftments have been shown to attenuate lung injury and fibrosis [17,18]. In our study, rASCs were detected in the rASCs treatment group but not in the saline group.…”
Section: Discussionsupporting
confidence: 52%
“…In many studies, ASC engraftments have been shown to attenuate lung injury and fibrosis [17,18]. In our study, rASCs were detected in the rASCs treatment group but not in the saline group.…”
Section: Discussionsupporting
confidence: 52%
“…The epithelial/ECM interaction is crucial for dedifferentiation and redifferentiation of the epithelial cells and in combination with degradation of the BM structures, they are implicated in epithelial migration. 39 B-1 subunit integrins contribute to the migration of epithelial cells on laminin and collagen type IV. 40 However, in large wounds, the cells' ability to migrate may not be sufficient to cover the entire wound area.…”
Section: Controlling Epithelial Cell Migrationmentioning
confidence: 99%
“…Thus, the mechanism of the repair of damaged epithelium has been widely studied. Epithelial progenitors termed Clara cells (transit-amplifying cells) are broadly distributed and after injury differentiate into ciliated cells [117,118]. In addition to Clara cells, bronchiolar airways have also rare stem cells that contribute to repair of the tissue [119].…”
Section: Pulmonary Epithelium Injurymentioning
confidence: 99%